Cloning and bacterial expression of the CYS3 gene encoding cystathionine gamma-lyase of Saccharomyces cerevisiae and the physicochemical and enzymatic properties of the protein. - Yamagata, S (1993)
By screening a yeast genomic library, we isolated and characterized a gene rescuing the cysteine requirement in a "cys1" strain of Saccharomyces cerevisiae. Except for four residues in the open reading frame composed of 1,182 nucleotides, the DNA sequence was the same as that for the CYS3 (CYI1) gene, encoding cystathionine gamma-lyase (EC 4.4.1.1), and isolated previously as a cycloheximide-induced gene (B. Ono, K. Tanaka, K. Naito, C. Heike, S. Shinoda, S. Yamamoto, S. Ohmori, T. Oshima, and A. Toh-e, J. Bacteriol. 174:pp.3339-3347, 1992). S. cerevisiae "cys1" strains carry two closely linked mutations; one (cys1) causes a defect in serine O-acetyltransferase (EC 2.3.1.30), and another, designated cys3, impairs cystathionine gamma-lyase activity. Rescue of the cysteine requirement by the gene encoding cystathionine gamma-lyase is consistent with both defects being responsible for the cysteine auxotrophy. In an effort to further determine the physicochemical and enzymatic properties of this enzyme, a coding fragment was cloned into an Escherichia coli expression plasmid, and the protein was produced in the bacteria. The induced protein was extracted by sonication and purified to homogeneity through one course of DEAE-cellulose column chromatography. The yield of the protein was approximately 150 mg from cells cultured in 1 liter of L broth. The protein showed molecular weights of approximately 194,000 and 48,000 (for the subunit), suggesting a tetrameric structure. An s20,w value of 8.8 was estimated by centrifugation in a sucrose concentration gradient. No sulfhydryl groups were detected, which is consistent with the absence of cysteine residues in the coding sequence. The isoelectric point was at pH 5.2. The protein showed a number of cystathionine-related activities, i.e., cystathionine beta-lyase (EC 4.4.1.8), cystathionine gamma-lyase, and cystathionine gamma-synthase (EC 4.2.99.9) with L-homoserine as substrate. In addition, we demonstrated L-homoserine sulfhydrylase (adding H2S) activity but could find no detectable serine O-acteyltransferease activity. In this paper, we compare the enzymatic properties of the protein with those of homologous enzymes previously reported and discuss the possibility that this enzyme has a physiological role as cystathionine Beta-lyase and cystathionine gamma-synthase in addition to its previously described role as cystathionine gamma-lyase.